Adaptability studies of garlic (Allium sativum) advanced lines - Raheel, Asfand; Raheel Babar, Hidayatullah; Ullah, Muhammad Arshad; Iqbal, Ali Zaffar, Maouz (Journal of Scientific Agriculture, 2019)
The purpose of this research was to identify the most desirable verities adopted in different environmental conditions of the country. Five garlic advance line; NARC Garlic-1, NARC Garlic-3, NARC Garlic-4, NARC Garlic-5 along with ‘Lehsan Gulabi’ as check were evaluated at different locations along with NARC, Islamabad. Different morphological parameters; plant height, plant girth, leaf number per plant and leaf width were studied at four different growth stages. NARC Garlic-1 performed better as compared other advance lines and control tested.